Has the inclusion of forward-looking statements in monetary policy communications made the Bank of Canada more transparent? - Christine Fay; Toni Gravelle (Bank of Canada, 2010)
To investigate the extent to which the transparency of the Bank of Canada's monetary policy has improved, the authors examine empirically - over the period 30 October 2000 to 31 May 2007 - the reaction of Canadian financial markets to official Bank communications, and in particular their reaction to the recent inclusion of forwardlooking policy-rate guidance in these communications. The authors find evidence that fixed announcement date (FAD) press releases, and, to a lesser extent, speeches by Governing Council members, significantly affect near-term interest rate expectations, indicating that central bank communication conveys important information to market participants. However, the authors' results also show that FAD press releases and speeches do not significantly impact market rates over the more recent period, when forward-looking statements have been used on a regular basis. The authors investigate two explanations for this change in response: (i) market participants better understand the Bank's monetary policy reaction function as they become accustomed to the FAD regime; or, (ii) market participants focus more on the forward-looking statements and less on the Bank's discussion of the economic outlook, and therefore respond less than before to new macroeconomic data releases. The authors find evidence to support the second explanation: forward-looking statements - even though they have been designed to be conditional - have made the Bank's decisions on the policy rate more predictable, but not necessarily more transparent.
Keywords: E52; E58; 330; Interest rates; Central bank research; Transmission of monetary policy; Geldpolitik; Zentralbank; Prognose; Ankündigungseffekt; Transmissionsmechanismus; Inflationsrate; Zins; Kanada